Foreign labourers in the construction industry: a study on the legal problems caused and faced by them in Malaysia / Nur Liyana Mohd Anuar and Zaffan Mohamed Yassin - Mohd Anuar, Nur Liyana; Mohamed Yassin, Zaffan (2008)
Large-scale labour migration has been taking place in Southeast Asia since the early 1980s and the wealthier countries in the region such as Malaysia rely heavily on foreign labourers to sustain their economic growth. Foreign labourers in Malaysia, estimated at 25 per cent of the labour force account for a significant proportion especially in the construction industry, factory and plantation workforces, as well as their involvement in the informal service sector and as domestic helpers. They are at the lower scale of the labour's hierarchy, have fewer protection and rights and are seen as an expendable workforce compared with the locals. However the presence of such a large, vulnerable group of labourers has good and bad implications for the Malaysian society. Therefore, we would like to study the adequacy of laws in relation to the rights of foreign labourers and deteniiining the legal problems caused and faced by these foreign labourers in the construction industry.